Distribution, Function, and Evolution of a Gene Essential for Trichothecene Toxin Biosynthesis in Trichoderma - Gutiérrez, Santiago; McCormick, Susan P.; Cardoza, Rosa E.; Kim, Hye-Seon; Yugueros, Laura Lindo; Vaughan, Martha Marie; Carro-Huerga, Guzmán; Busman, Mark; Sáenz de Miera, Luis E.; Jaklitsch, Walter M.; Zhuang, Wen-Ying; Wang, Chao; et al. (Frontiers in Microbiology, 2021)
Trichothecenes are terpenoid toxins produced by species in 10 fungal genera, including two species of Trichoderma. The trichothecene biosynthetic gene (tri) cluster typically includes the tri5 gene, which encodes a terpene synthase that catalyzes formation of trichodiene, the parent compound of all trichothecenes. The two Trichoderma species, Trichoderma arundinaceum and T. brevicompactum, that have been examined are unique in that tri5 is located outside the tri cluster in a genomic region that does not include other known tri genes. In the current study, analysis of 35 species representing a wide range of the phylogenetic diversity of Trichoderma revealed that 22 species had tri5, but only 13 species had both tri5 and the tri cluster. tri5 was not located in the cluster in any species. Using complementation analysis of a T. arundinaceum tri5 deletion mutant, we demonstrated that some tri5 homologs from species that lack a tri cluster are functional, but others are not. Phylogenetic analyses suggest that Trichoderma tri5 was under positive selection following its divergence from homologs in other fungi but before Trichoderma species began diverging from one another. We propose two models to explain these diverse observations. One model proposes that the location of tri5 outside the tri cluster resulted from loss of tri5 from the cluster in an ancestral species followed by reacquisition via horizontal transfer. The other model proposes that in species that have a functional tri5 but lack the tri cluster, trichodiene production provides a competitive advantage.